Larynx-preserving limited resection with total thoracic esophagectomy and gastric pull-up reconstruction: A promising treatment for selected cervical esophageal squamous cell carcinoma - Wang, Wu-ping; Ma, Jie; Lu, Qiang; Han, Yong; Li, Xiao-fei; Jiang, Tao; Zhao, Jin-bo (Turkish Journal of Gastroenterology, 2020)
Background/Aims: There is no consensus on treatment for cervical esophageal squamous cell carcinoma (ESCC) . Our purpose was to evaluate the feasibility and outcome of larynx-preserving limited resection with total thoracic esophagectomy and gastric pull-up reconstruction for the treatment of cervical ESCC without tumor involvement of the larynx and hypopharynx.Materials and Methods: Retrospective analysis of consecutive patients with cervical ESCC who underwent R0 surgical resection from 2006 to 2011 in our center was performed. Kaplan–Meier method was used to calculate the patients’ survival.Results: In total, 74 cervical ESCC were enrolled in the study. the mortality rate in 30 days was 8.1%，the total complication rate (at least one ) was 47.3%，the anastomosis leakage occurrence was 37.8%, the mechanical ventilation rate was 12.2%, the rate of normal oral diet within 15 days was 71.6%, and the anastomosis recurrence rate in follow-up was 8.1%. The detailed analysis showed that the anastomosis leakage, pulmonary infection, laryngeal recurrent nerve injury and chylothorax were the most common four complications in those surgical patients. Finally, the survival data showed that the median survival time was 31.83 months (95% CI = 12.39 - 51.28 months), and the 3 years, 5 years survival rate was 49.1% and 35.5%, respectively.Conclusion: Larynx-preserving limited resection with total thoracic esophagectomy and gastric pull-up reconstruction might be a feasible and effective surgical alternative for selected cervical ESCC patients whose tumor without involvement of the larynx and hypopharynx.